FAKTOR-FAKTOR YANG MEMPENGARUHI KESIAPAN PEMERINTAH DAERAH DALAM PENERAPAN PP NOMOR 12 TAHUN 2019 DENGAN GAYA KEPEMIMPINAN SEBAGAI VARIABEL MODERASI (STUDI EMPIRIS PADA ORGANISASI PERANGKAT DAERAH PROVINSI RIAU) - Widya Arisza Septyaningtyas; Taufeni Taufik; Muhammad Rasuli (Institut Bisnis dan Teknologi Pelita Indonesia, 2022)
ABSTRACT The purpose of this research was to identify and analyze the influence of human resource competence, communication, information technology, organizational commitment, organizational culture, and professionalism on local government’s readiness in the implementation of Government Regulation Number 12 Year 2019 with Leadership Style as moderating variable. The population in this research was all 33 Regional Apparatus Organizations in Riau Province. This research used the Census Sampling method with total number of 165 respondents. The data was analysis using SEM-PLS with WarpPLS software. The results showed that that the competence of human resources, communication, information technology, organizational commitment, and professionalism have influence on local government’s readiness in the implementation of Government Regulation Number 12 Year 2019, while organizational culture has no influence on local government’s readiness in the implementation of Government Regulation Number 12 Year 2019. Another result showed that leadership style strengthens the relationship between human resource competence, communication, information technology, organizational culture, and professionalism on local government’s readiness in the implementation of Government Regulation Number 12 Year 2019, while leadership style does not strengthen the effect of organizational commitment on local government’s readiness in the implementation of Government Regulation Number 12 Year 2019. ABSTRAK Penelitian ini bertujuan untuk mengidentifikasi dan menganalisis terkait pengaruh kompetensi sumber daya manusia, komunikasi, teknologi informasi, komitmen organisasi, budaya organisasi, dan profesionalisme terhadap kesiapan pemerintah daerah dalam penerapan PP Nomor 12 Tahun 2019 dengan gaya kepemimpinan sebagai variabel moderasi. Populasi dalam penelitian ini adalah seluruh Organisasi Perangkat Daerah (OPD) di lingkungan Pemerintah Provinsi Riau yang berjumlah 33 Organisasi Perangkat Daerah (OPD). Pada penelitian ini, peneliti menggunakan metode Sampling Jenuh dengan jumlah responden sebanyak 165 responden. Analisis Data menggunakan SEM-PLS dengan software WarpPLS. Hasil penelitian menunjukkan bahwa kompetensi sumber daya manusia, komunikasi, teknologi informasi, komitmen organisasi, dan profesionalisme berpengaruh terhadap kesiapan pemerintah daerah dalam penerapan PP Nomor 12 Tahun 2019, sedangkan budaya organisasi tidak berpengaruh terhadap kesiapan pemerintah daerah dalam penerapan PP Nomor 12 Tahun 2019. Hasil lain menunjukkan bahwa gaya kepemimpinan memperkuat hubungan antara kompetensi sumber daya manusia, komunikasi, teknologi informasi, budaya organisasi, dan profesionalisme terhadap kesiapan pemerintah daerah dalam penerapan PP Nomor 12 Tahun 2019, sedangkan gaya kepemimpinan tidak memperkuat pengaruh antara komitmen organisasi terhadap kesiapan pemerintah daerah dalam penerapan PP Nomor 12 Tahun 2019.